Forms of Parent-Child Attachments Possessed Among Grade 10 Learners in South Africa - Morefaith Naledi Sibanyoni; Peter J.O. Aloka (Social Sciences and Education Research Review, 2025)
The study aimed to investigate forms of parent-child attachments possessed among Grade 10 Learners in Sedibeng West Township schools, South Africa. A multiple case study research design was utilized. The sampling frame comprised 6 Life-Orientation teachers, 18 grade 10 learners, and 3 deputy principals from 3 selected secondary schools in the Sedibeng West district. Six Life-Orientation teachers, that is two from each school, were chosen using a purposive sampling technique. Data collection from all participants was conducted using semi-structured interviews. The data obtained from interviews was analyzed thematically. The findings revealed that learners exhibited both secure and insecure attachment types in their home environments. The findings also indicated that secure learners possess qualities such as self-assurance, respectfulness, confidence, active participation in class, and proficiency in both formal and informal assessments. The findings indicated that the learners exhibited diverse insecure attachment styles within their households. The study recommended training parents in effective parenting techniques and raising awareness in the community about creating secure homes.